Quality and image: The role of satisfaction and trust as intervening variables on loyalty of customer’s internet service providers - Teuku Meldi Kesuma; Mukhlis Yunus; M. Ridha Siregar; Abdul Muzammil (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
Many factors can affect customer loyalty that some of them are service quality and corporate image. There are two objectives of this study. First, this study explains service quality and corporate image effects as antecedents for customer satisfaction, trust, and loyalty. Second, this study investigates the role of customer satisfaction and trust in mediating the service quality and corporate image effects on customer loyalty in the context of ISP customers. By using the purposive sampling technique, this study researched 270 ISP customers. The sample of data was statistically analyzed with the Structural Equation Modeling (SEM) and the Confirmatory Factor Analysis (CFA). This study confirmed that customer satisfaction, customer trust, and loyalty were directly affected by service quality and corporate image. Customer satisfaction and customer trust influenced customer loyalty significantly. The role of customer satisfaction and customer trust indirectly in mediating service quality and corporate image effects on customer loyalty was also confirmed by partial mediation. This study concludes by arguing that it needs to pay attention to service quality and the company’s good name levels to maintain customer loyalty.